VD_FINDINFO Jug / 2021 / 269 vom 5. November 2020 - VD Tribunal cantonal (2020)
IN DUBIO PRO REO, VOLDROIT PÉNAL, ABUS DE CONFIANCE, DÉTÉRIORATION DE DONNÉES, PHARMACIEN | 138 CP, 139 CP, 144bis CP, 47 CP, 10 CPP (CH)